2022
DOI: 10.1001/jamanetworkopen.2022.8526
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination and Estimated Public Health Impact in California

Abstract: Key Points Question How many COVID-19 cases, hospitalizations, and deaths were averted because of COVID-19 vaccination in California? Findings In this modeling study using data from the California Department of Public Health, COVID-19 vaccination was estimated to have prevented more than 1.5 million COVID-19 cases, 72 000 hospitalizations, and 19 000 deaths during the first 10 months of vaccination, through October 16, 2021. Meaning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Previous literature also found that the COVID-19 pandemic in the United States was characterized by a geographically localized mosaic of transmission along an urban-rural gradient ( 8 - 9 ), suggesting that geographic distance may play an important role in SARS-CoV-2 spread. Finally, the public health impact of COVID-19 vaccines has already been widely discussed in the literature ( 10 - 13 ) and our study confirms previous evidence.…”
Section: Discussionsupporting
confidence: 91%
“…Previous literature also found that the COVID-19 pandemic in the United States was characterized by a geographically localized mosaic of transmission along an urban-rural gradient ( 8 - 9 ), suggesting that geographic distance may play an important role in SARS-CoV-2 spread. Finally, the public health impact of COVID-19 vaccines has already been widely discussed in the literature ( 10 - 13 ) and our study confirms previous evidence.…”
Section: Discussionsupporting
confidence: 91%
“…Pakistan has reported about 1.5 million cases of COVID-19 and nearly 31,000 deaths [2, 3]. COVID-19 vaccines have had a significant impact on controlling both morbidity and mortality from COVID-19 [4, 5]. The proportion of deaths to cases changed greatly throughout the pandemic with reduced disease severity after vaccines were introduced and the evolution of SARS-CoV-2 variants of concern (VoC) toward higher transmissibility and lower pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 vaccines included formulations based on mRNA expression of spike protein, adenovirus vector-based vaccines, and inactivated vaccine types (2). They have had a major impact on controlling both morbidity and mortality from COVID-19 (3, 4), leading to what in 2022 is thought to be the tail end of the pandemic (5).…”
Section: Introductionmentioning
confidence: 99%